MOTIVASI SISWA MEMILIH PENDIDIKAN FORMAL BERBASIS AGAMA DI MADRASAH ALIYAH RAUDHATUL ULUM DESA PUGUK KECAMATAN SUNGAI AMBAWANG - Zeini, Muhammad (Jurnal Pendidikan Sosiologi dan Humaniora, 2018)
The title of this research is "Student Motivation Choosing Formal Education Based on Religion in Madrasah Aliyah Raudhatul Ulum Puguk Village Sungai Ambawang District". The purpose of this research is to describe the intrinsic motivation of students in choosing Formal based religious education in Madrasah Aliyah Raudhatul Ulum Puguk Village and extrinsic motivation of students in choosing Formal-based religious education at Madrasah Aliyah Raudhatul Ulum Puguk Village. The approach methods which this research use are qualitative approach with descriptive methods. The data collection technic which this research used are observation, interviews and documentation analysis with data collection tools in from of observation guidline, interview guidline and documentation. This research result indicates that motivation formal education students vote based religion in Madrasah Aliyah Raudhatul Ulum because the thrust emerged from students (intrinsic) which includes interest and passion, ideals, and equality culture and motivation emerging from outside themselves students (extrinsic) caused the role of parents, want to get award and praise, the role of the his tutor, environmental conditions as well as economic factors their parents. Based on observations, interviews and documentation that researchers have conducted, proves that intrinsic motivation and extrinsic motivation encourage students to choose a religious based formal education in Madrasah Aliyah Raudhatul Ulum Puguk Village Sungai Ambawang District.